Isatin endowed metal chelates as antibacterial and antifungal agents - Khalid, Seher; Sumrra, Sajjad Hussain; Chohan, Zahid Hussain (Penerbit Universiti Kebangsaan Malaysia, 2020)
A new series of 5-chloroindoline-2,3-dione (isatin) derived ligands (L1 )-(L4 ) were prepared by reacting isatin with various diamines such as ethane-1,2-diamine, propane-1,3-diamine, butane-1,4-diamine, and benzene-1,2-diamine in an equimolar ratio to give 3-[(2-aminoethyl)imino]-5-chloro-1,3-dihydro-2H-indol-2-one (L1 ), 3-[(3-aminopropyl) imino]-5-chloro-1,3-dihydro-2H-indol-2-one (L2 ), 3-[(4-aminobutyl)imino]-5-chloro-1,3-dihydro-2H-indol-2-one (L3 ) and 3-[(2-aminophenyl)imino]-5-chloro-1,3-dihydro-2H-indol-2-one (L4 ). All ligands acted as tridentate possessing three active sites, isatin-O, azomethine-N, and amino-N for binding with the metal atoms. The structures of the isatin based Schiff bases were elucidated through their spectral (infrared, ultraviolet, nuclear magnetic resonance, and mass spectra), physical (melting point and solubility) and analytical (C, N, H %) data. The prepared ligands were reacted with Co(II), Ni(II), Cu(II), and Zn(II) transition metals in 1:2 molar ratio (metal:ligand) to form their complexes. IR, UV, NMR, conductance, magnetic moment, and elemental analysis was used to characterize the metal complexes. Metals based isatins were evaluated for their in-vitro antimicrobial properties against selected fungal and bacterial species. The anti-bacterial and anti-fungal results showed the metal chelates to be more biologically active than their parent uncomplexed ligands.